Challenging gender norms in an African Pentecostal denomination - Jacobs, Phumeza C.N.; Naidoo, Marilyn (Hervormde teologiese studies, 2025)
Women’s exclusion from leadership positions in African Pentecostal churches is a serious problem that affects the church and society at large. Gender inequality in religious spaces often mirrors societal power dynamics, which, if unaddressed, hinders national progress and the resolution of pressing social issues. This article reports on a study within a South African Pentecostal denomination, where women continue to be denied ordination and are systematically marginalised from senior leadership structures. Findings reveal how literalist interpretations of scripture, patriarchal expressions of African masculinity and historical denominational practices converge to marginalise women in African Pentecostal churches. These interpretations uphold hegemonic gender norms that restrict women’s participation in spaces of ecclesial authority and decision-making. This article demonstrates how embedded theological paradigms and inherited church practices continue to reproduce male-dominated leadership models. Contribution: This article contributes to African Pentecostal feminist theological discourse by exposing the intersection of patriarchal theology and African cultural traditions in shaping gender exclusion. It calls for a reimagining of theology that embraces inclusivity, contextual sensitivity and justice. By advancing conversations around women’s leadership development, the study presents a vision for ecclesial transformation in which women’s full participation is integral to the mission and vitality of the church.